Mass balance of heavy metals in Celje area - Gorazd Žibret (Geologija, 2002)
The research which included sampling of attic dust and soils in the town Celje has shown that the environment is contaminated with heavy metals, especially with zinc and cadmium. That is a consequence of 100 years of smelting the sphalerite ore in Cinkarna Celje. With the data, that includes concentration of heavy metals in the attic dust on 99 points and the weight of air deposit on 19 points in Celje and its suburbs, is possible to calculate the emissions of heavy metals in the environment. With the help from data of geochemical background is possible to estimate the anthropogenic emissions. The calculationsshow, that these emissions of zinc in Celje is 1712 tons and the natural background has been estimated at 207 tons. The similar proportion between anthropogenic and natural emissions can be seen at cadmium (9,1 tons of anthropogenic and 1,4 tons of natural cadmium). The opposite ratio is seen by elements whoose presence is influenced mainly by lithology, for example aluminium (1388 tons of anthropogenic and 11540 tons of natural aluminium.